UV-B affects the immune system and promotes nuclear abnormalities in pigmented and non-pigmented bullfrog tadpoles - Franco-Belussi, Lilian [UNESP]; Fanali, Lara Zácari [UNESP]; De Oliveira, Classius [UNESP] (Elsevier, 2018)
Ultra-Violet (UV) radiation is a stressor of the immune system and causes DNA damage. Leukocytes can change in response to environmental changes in anurans, making them an important biomarker of stressful situations. The initial barrier against UV in ectothermic animals is melanin-containing cells in skin and in their internal organs. Here, we tested the effects of UV exposure on immune cells and DNA integrity in pigmented and non-pigmented tadpoles of Lithobates catesbeianus. We used an inflammation model with lipopolysaccharide (LPS) of Escherichia coli to test synergic effects of UV and LPS. We tested the following hypotheses: 1) DNA damage caused by UV will be more pronounced in non-pigmented than in pigmented animals; 2) LPS increases leukocytes in both pigmented and non-pigmented animals by systemic inflammation; 3) The combined LPS and UV exposure will decrease the number of leukocytes. We found that the frequency of immune cells differed between pigmented and non-pigmented tadpoles. UV exposure increased mast cells and DNA damage in erythrocytes in both pigmented and non-pigmented tadpoles, while leukocytes decreased after UV exposure. Non-pigmented tadpoles experienced DNA damage and a lower lymphocyte count earlier than pigmented tadpoles. UV altered immune cells likely as a consequence of local and systemic inflammation. These alterations were less severe in pigmented than in non-pigmented animals. UV and LPS increased internal melanin in pigmented tadpoles, which were correlated with DNA damage and leukocytes. Here, we described for the first time the effects of UV and LPS in immune cells of pigmented and non-pigmented tadpoles. In addition, we demonstrated that internal melanin in tadpoles help in these defenses, since leukocyte responses were faster in non-pigmented animals, supporting the hypothesis that melanin is involved in the initial innate immune response.
Keywords: DNA damage; Internal melanin; Leukocytes; Tadpoles; UV radiation